Development of Chinese —Turkish Relations under “One Belt, One Road” Initiative - J. Tao (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
China and Turkey — countries located at the two ends of the ancient trade Silk Road, which at the beginning of the 21st century were again closely linked by the Chinese initiative “One Belt, One Road”, are considered in the article. It is shown how these two economies with high economic activity complement each other’s needs and benefits. Attention is paid to the interaction and cooperation between them in such areas as the development of contacts on political issues, road communications, trade, money circulation, communication between people. It is stated that China and Turkey have achieved certain successes in promoting sustainable and stable development of bilateral relations. The authors also note that there are many challenges faced by both sides in implementing “One Belt, One Road” Initiative. It is emphasized that in terms of geopolitics, foreign policy and foreign economic relations, Turkey is in a rather difficult situation, cooperation between China and Turkey within the framework of “One Belt, One Road” also contains many risks. It is concluded that as long as the two countries adhere to the idea of reviving the Great Silk Road and a pragmatic approach, more and more mutually beneficial cooperation between China and Turkey will move forward.